2021
DOI: 10.1177/03000605211055618
|View full text |Cite
|
Sign up to set email alerts
|

Profile of serum cytokine concentrations in patients with gouty arthritis

Abstract: Objective This study aimed to analyze the changes in serum inflammatory cytokines and anti-inflammatory cytokines in patients with gouty arthritis (GA). Methods The clinical data and serum samples in patients with gouty arthritis and those in healthy volunteers were collected in China-Japan Friendship Hospital from July 2018 to January 2019. Serum cytokine concentrations in patients with GA and volunteers (controls) were determined by a chemiluminescence method. The differences in cytokine concentrations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…However, we did not find increased numbers of circulating IFN-g + T cells in gout condition (Fig. 4), consistent with recent reports (114,115). Similarly, we did not find significant differences in IL-17-production by T cells (data not shown), despite previous studies reporting increased levels of Th17-related cytokines in gout (41,42).…”
Section: Discussionsupporting
confidence: 92%
“…However, we did not find increased numbers of circulating IFN-g + T cells in gout condition (Fig. 4), consistent with recent reports (114,115). Similarly, we did not find significant differences in IL-17-production by T cells (data not shown), despite previous studies reporting increased levels of Th17-related cytokines in gout (41,42).…”
Section: Discussionsupporting
confidence: 92%
“…A study of 91 participants showed that serum IFN-g is not elevated in hyperuricemia and gout patients (43), which contrasts another recent study of 240 participants showing that IFN-g is significantly elevated in the gout remission stage (44). Therefore, these seemingly contradictory results demand further investigation.…”
Section: Discussionmentioning
confidence: 83%
“…Studies have shown that IL-6 is associated with the presence of gouty stones and joint deformities and serves as a prognostic indicator of disease progression in gout. 33,34 Moreover, it was demonstrated that IL-6 induced osteoclast formation. 35 Wenjing Xu et al 36 found that reducing IL-6 secretion through drug intervention could alleviate the symptoms of gout flare.…”
Section: Jak/stat Signaling Pathwaymentioning
confidence: 99%